Global model of intelligence and memorizing of information from conception until a child starts to walk for the period from 2009 until 2020. - Vidučić, Vinko (Array, 2009)
This paper's objective has been an analysis of the sustainable development of Croatia's maritime tourism. In order to define the main characteristics and determinants of the maritime tourism, a model of growth has been used. The evaluation and analysis of the relevant variables and the resulting growth rates have been aimed at a scientific formulation of the results of the sustainable development analysis of the maritime tourism in the Republic of Croatia. The basic hypothesis has been confirmed through the direct growth rates of the chosen model variables. In this way a scientifically based confirmation of the hypothesis has been provided. Namely, it has been confirmed that, based on scientific insights into the sustainable development of the maritime tourism, it is possible to suggest a new model of its sustainable development in Croatia for the period 2007 – 2015.